Uncharted territory - environment and population beyond six billion - Richard Elliot Benedick (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
When historians in the far distant future look back upon the tumultuous twentieth century, they will likely judge the most outstanding feature to be the extraordinary increase in human numbers that has occurred during this relatively short time period. It took the entire history of humanity – tens of thousands of years – for the world's population to reach one billion, which is now estimated to have occurred around 1804. It was more than a century later that the second billion was reached. But it took only 12 years – from 1987 to 1999 – for the most recent billion, the sixth, to be added. The world has never seen anything like the steep population growth of the twentieth century, with most of it concentrated during the last fifty years.
Keywords: 300; Bevölkerungswachstum; Umweltbelastung; Wald; Wassermangel; Klimaveränderung; Bevölkerungspolitik